Epidemiological Risk Factors Associated with the Occurrence of Clinical and Subclinical Bovine Mastitis and Their Causal Association - R Navaneethan; S Saravanan; P Suresh (Research Perspectives of Microbiology and Biotechnology Vol. 2, 2024)
The study aims at reporting the various epidemiological risk factors associated with the occurrence of clinical and subclinical bovine mastitis and their causal association. Enhanced milking hygiene, implementation of post-milking teat disinfection, maintenance of milking machines are some of the measures to prevent bovine mastitis. The prevalence of clinical and subclinical mastitis associated with the various epidemiological risk factors and their extent of association was studied based on the positivity of 454 mastitic milk samples by polymerase chain reaction (PCR), collected from clinical and subclinical mastitic cows which were brought to Veterinary College and Research Institute (VC&RI), Namakkal, TamilNadu. The prevalence of clinical mastitis was high in cows at 4th lactation and above (55.8%, OR-3.37), late lactation (65.3%, OR-5.55), of H-F cross (39.0%, OR-1.81), with previous incidence of mastitis (48.5%), under concrete bedding (30.4%, OR-0.99), without practice of pre-teat dipping (41.3%, OR-28.0), with post-teat dipping (39.8%, OR-0.06), under hand milking (34.0%) and in winter season (41.3%, OR-2.50). The prevalence of subclinical mastitis was high in cows at 4th lactation and above (44.1%, OR-2.99), late lactation (34.6%, OR-2.93), of other breeds (29.7%, OR-1.46), under soil bedding (24.9%, OR-1.60), without practice of pre-teat dipping (31.9%, OR-58.59), with post-teat dipping (28.5%, OR-0.24), under hand milking (23.0%) and in winter season (34.4%, OR-2.9). The high prevalence recorded in cows without practice of pre teat dipping could be associated with more chances for spread of Staphylococcus spp. from skin of teats into the teat canals. Whereas, the high prevalence recorded in cows with practice of post-teat dipping could be associated with the poor efficiency of teat dipping to eliminate Staphylococci which already colonized the teat canals and also inefficient concentration of sanitizer used by farmers. Statistically, the prevalence of clinical and subclinical mastitis was statistically significant in cows between ages of lactation, stages of lactation and seasons, whereas, statistically no significant difference could be observed between breeds of cows. Regular diagnosis and treatment of subclinical mastitis at an early stage during lactation period could help in preventing development of clinical mastitis in a herd.